KROSS–SAMI: a direct IFS comparison of the Tully–Fisher relation across 8 Gyr since z ≈ 1. Issue 2 (17th October 2018) - Tiley, A L; Bureau, M; Cortese, L; Harrison, C M; Johnson, H L; Stott, J P; Swinbank, A M; Smail, I; Sobral, D; Bunker, A J; Glazebrook, K; Bower, R G; et al.
ABSTRACT: We construct Tully–Fisher relations (TFRs), from large samples of galaxies with spatially resolved H α emission maps from the K-band Multi-Object Spectrograph (KMOS) Redshift One Spectroscopic Survey (KROSS) at z ≈ 1. We compare these to data from the Sydney-Australian-Astronomical-Observatory Multi-object Integral-Field Spectrograph (SAMI) Galaxy Survey at z ≈ 0. We stringently match the data quality of the latter to the former, and apply identical analysis methods and sub-sample selection criteria to both to conduct a direct comparison of the absolute K -band magnitude and stellar mass TFRs at z ≈ 1 and 0. We find that matching the quality of the SAMI data to that of KROSS results in TFRs that differ significantly in slope, zero-point, and (sometimes) scatter in comparison to the corresponding original SAMI relations. These differences are in every case as large as or larger than the differences between the KROSS z ≈ 1 and matched SAMI z ≈ 0 relations. Accounting for these differences, we compare the TFRs at z ≈ 1 and 0. For disc-like, star-forming galaxies we find no significant difference in the TFR zero-points between the two epochs. This suggests the growth of stellar mass and dark matter in these types of galaxies is intimately linked over this ≈8 Gyr period.